Effect of Acid Catalyst on Epoxydation Reaction of Nyamplung Seed Oil - Saputri, Dita Ayu; Suhendra, Dedy; Gunawan, Erin Ryantin; Murniati, Murniati (Jurnal Pijar Mipa, 2025)
Epoxy is a cyclic ether compound that contains an oxirane group and has been widely applied as a stabilizer, plasticizer in polyvinyl chloride (PVC), surfactant, pesticide raw material, and as a polymer resin coating. The raw materials in epoxy synthesis come from petroleum derivatives, which are non-renewable natural resources. Therefore, there is a need for alternative raw materials that can be renewed, such as vegetable oil. In this study, nyamplung seed oil was used. Epoxy synthesis is usually carried out using carboxylic acid epoxidation with the help of an acid catalyst. This research aims to determine the effect of the type of acid catalyst and its concentration on the epoxidation reaction of nyamplung seed oil and the characterization of the epoxy produced. The research results show that using an acid catalyst can increase the formation of oxirane groups at a certain concentration, where the highest oxirane number value was obtained when using the H2SO4 catalyst, namely 3.15%. The resulting epoxy is pale yellow, has a typical absorption area (COC) at a wave number of 825 cm-1, an iodine value of 13.96 g iod/100 g, a viscosity of 20.80 cP, and a relative per cent conversion to oxirane of 73.4 %